Rancangan Digitalisasi Pemerintah Sumut - Nasution, Zulia Lestari; Sitorus, Silfia Ramadhani (Journal of Computer Science and Informatics Engineering, 2025)
Government digitalization has become an essential need in enhancing efficiency, transparency, and accessibility of public services. This study aims to design a digitalization strategy for the North Sumatra Provincial Government to support more effective services. The methods used include technology needs analysis, literature review, and surveys among the community and government employees. The findings indicate that developing digital infrastructure, integrated service applications, and human resource training are key success factors. This article proposes a digitalization implementation model tailored to local needs, emphasizing collaboration among the government, community, and private sector. The conclusion highlights that digitalization can improve service efficiency and foster bureaucratic transformation in North Sumatra.